Optimalisasi Greenpreneurship melalui Edukasi Eco-Friendly Packaging pada Pelaku Usaha Makanan Tradisional Wilayah Rungkut Surabaya Timur: Pengabdian - Nurul Iman; Elly Yuniar Nitawati; Sari Handayani; Ahmad Zainuddin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to optimize the practice of greenpreneurship through education on the use of eco-friendly packaging among traditional food business owners in the Rungkut area of East Surabaya. The main problems faced by MSMEs are the low level of environmental awareness and the widespread use of single-use plastic packaging. This activity was carried out through interactive workshops, practical simulations, and the formation of a post-training community. A total of 38 participants were involved, and the results of the pre-test and post-test showed a 43.8% increase in understanding scores. As many as 55.3% of participants adopted at least one type of eco-friendly packaging within the first two weeks after the activity. In addition, 84.2% of participants joined the Green MSME Rungkut community to strengthen networks, share best practices, and maintain the sustainability of the program. This activity demonstrates that a practice-based educational approach combined with community support is effective in encouraging sustainable behavioral change among MSME actors. The results of this community service are expected to serve as a model that can be replicated in other areas to build a more environmentally friendly and competitive business ecosystem.